Pemodelan Estimasi Biaya Elemen Struktur Bangunan Rumah Toko Dengan Variasi Lebar Bentang - Nadia Diandra; Stephen Valentino; Billy Chandra; Vincentius Hartanto (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
The development of construction will affect work methods in construction, design and materials. Changes in design, materials and work methods in the construction of a construction project will affect the costs that must be incurred by the owner and the time required to construct a building. Conceptual cost estimation is needed as a reference or guide in determining the policies used to determine the amount of investment that must be implemented. Planning is the initial stage in construction development activities. Effective and efficient project planning is needed in carrying out a project. Along with the need for efficiency, the cost estimation model at the early stages of project planning must be accurate so that the results can be accounted for. This study aims to obtain an estimate of the structural cost of a shop house building with several span variations. Variations in the width of the shop house are 5 m, 6.67 m and 8 m. The research results obtained that the cost of the structure on the 8 m span is Rp. 2,352,485,387, the 8 m span is the span that has the largest cost compared to other spans. The difference between the span of 8 m and the span of 6.67 m and 5 m is Rp. 93,480,110 and Rp. 13,740,263, respectively. Based on these results it was concluded that the larger the span, the greater the costs required. This is influenced because there are differences in the dimensions and specifications of the structures used in each span.